EVALUATION OF RISK MANAGEMENT STRATEGIES IN THE CRICKET CULTIVATION INDUSTRY: SWOT ANALYSIS APPROACH - Suwandi, Suwandi; Pranata, Sudadi; Ayu Lestari, Ni Wayan Fitriana; Kartika, Ika (LPPM Universitas Malikussaleh, 2024)
The cricket cultivation industry has become a significant part of the MSME sector in many countries. However, this sector is also faced with various risks that can affect the business continuity and growth of the MSMEs involved in it. This research aims to evaluate the risk management strategies used by MSMEs in the cricket cultivation industry, using a SWOT analysis approach. Data was collected through surveys and interviews with cricket cultivation MSME owners in the Banjarwangunan Village area, Mundu District - Cirebon Regency. The analysis is carried out by identifying the strengths, weaknesses, opportunities and threats faced by these MSMEs in managing the risks related to their business. It is hoped that the results of this research will provide in-depth insight into the effectiveness of existing risk management strategies, as well as provide recommendations for increasing the success and resilience of cricket cultivation MSMEs in facing existing challenges.